No Time-Dependent Effects of Psychosocial Stress on Fear Contextualization and Generalization: A Randomized-Controlled Study With Healthy Participants. (December 2019) - Sep, Milou S. C.; Gorter, Rosalie; van Ast, Vanessa A.; Joëls, Marian; Geuze, Elbert
The formation of context-dependent fear memories (fear contextualization) can aid the recognition of danger in new, similar, situations. Overgeneralization of fear is often seen as hallmark of anxiety and trauma-related disorders. In this randomized-controlled study, we investigated whether exposure to a psychosocial stressor influences retention of fear contextualization and generalization in a time-dependent manner. The Trier Social Stress Test was used to induce psychosocial stress. Healthy male participants (n = 117) were randomly divided into three experimental groups that were subjected to the acquisition phase of the Fear Generalization Task: (1) without stress, (2) immediately after acute stress, or (3) 2 h after acute stress. In this task, a male with neutral facial expression (conditioned stimuli) was depicted in two different contexts that modulated the conditioned stimuli–unconditioned stimuli (=shock) association (threat, safe). Salivary alpha-amylase and cortisol levels were measured throughout the experiment. After a 24-h delay, context-dependency of fear memory was investigated with an unannounced memory test consisting of the threat and safe contexts alternated with a novel context (the generalization context). Multilevel analyses revealed that participants showed increased fear-potentiated startle responses to the conditioned stimuli in the threat compared to the safe context, at the end of the acquisition phase, indicating adequate fear contextualization. Directly after acquisition, there were no time-dependent effects of psychosocial stress on fear contextualization. Context-dependency of fear memories was retained 24 h later, as fear-potentiated startle responding was modulated by context (threat > safe or novel). At that time, the context-dependency of fear memories was also not influenced by the early or late effects of the endogenous stress response during acquisition. These results with experimental stress deviate in some aspects from those earlier obtained with exogenous hydrocortisone administration, suggesting a distinct role for stress mediators other than cortisol.